The role of women in empowering economic prosperity through domestic credit in the Southern African Development Community (SADC) - Ngollo, Magwana Ibrahim; Mwombeki, Frank Arbogast; Mwenda, Beny Benjamin (Economic Journal of Emerging Markets, 2026)
Purpose — This study examines the symbiotic relationship between women's representation in parliament and domestic credit, and the direct and indirect pathways by which these factors influence economic prosperity in Southern African Development Community (SADC) countries.Methods — Panel data from 16 SADC countries over the period 1997 -2022 are analysed using Generalised Method of Moments (GMM) and Generalised Structural Equation Modelling (GSEM), with a focus on the examination of interaction effects and diminishing returns of women’s parliamentary representation and domestic credit on economic prosperity.Findings — The results indicate that women’s representation in parliament has a significant positive effect on economic prosperity, with the effect strengthened by domestic credit. Domestic credit also contributes indirectly to economic growth by enhancing women’s economic influence.Implication — These findings provide important insights for policymakers, highlighting the need for a balanced strategy that promotes both women’s political participation and financial inclusion while avoiding potential economic imbalances.Originality — This study contributes to the literature by integrating gender, finance, and economic growth within the SADC context and by uncovering indirect pathways through which domestic credit affects economic prosperity via women’s political empowerment.